2021
DOI: 10.1007/s00402-021-04078-6
|View full text |Cite
|
Sign up to set email alerts
|

High-stress distribution in the lateral region of the subtalar joint in the patient with chronic lateral ankle instability

Abstract: Purpose Chronic lateral ankle instability (CLAI) is associated with osteoarthritis (OA). However, the characteristics of patients with CLAI who progress to OA are not clear. Measurement of Hounsfield Unit (HU) value on computed tomography (CT) is reported to be useful to evaluate the stress distribution. We aimed to evaluate the stress distribution in the ankle and subtalar joints and factors enhancing it in patients with CLAI. Materials and methods Thirty-three ankles with CLAI (CLAI group) and 26 ankles with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 36 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…20,29 However, a previous study reported that excessive stress to the lateral region of the ankle and subtalar joints might result if the CFL is not repaired, leading to ankle and subtalar joint arthritis. 3,25 Hunt et al 12 reported that a loose or incompetent CFL potentially mitigates long-term consequences, such as ankle or subtalar joint arthritis, indicating that the CFL repair may be beneficial during lateral ankle ligament repair. Several studies also found better stability after a combined ATFL and CFL repair than ATFL repair alone because CFL plays an essential role in resisting ankle inversion in the coronal plane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,29 However, a previous study reported that excessive stress to the lateral region of the ankle and subtalar joints might result if the CFL is not repaired, leading to ankle and subtalar joint arthritis. 3,25 Hunt et al 12 reported that a loose or incompetent CFL potentially mitigates long-term consequences, such as ankle or subtalar joint arthritis, indicating that the CFL repair may be beneficial during lateral ankle ligament repair. Several studies also found better stability after a combined ATFL and CFL repair than ATFL repair alone because CFL plays an essential role in resisting ankle inversion in the coronal plane.…”
Section: Discussionmentioning
confidence: 99%
“…7,10 In addition, CLAI can lead to osteoarthritis (OA) because of the abnormal high-stress distribution in the ankle and subtalar joints. 25,38 Therefore, mechanical instability should be eliminated to prevent OA development. With recent advances in technology, surgeons are showing more interest in arthroscopic procedures, and their clinical outcomes are comparable to those of traditional open Broström procedures.…”
Section: Introductionmentioning
confidence: 99%
“…It lacks self-healing ability when damaged, and in clinical practice, it usually manifests as persistent ankle pain. 24,25 As the injury gradually worsens, it will affect the upper surface of the talus, causing greater and irreversible damage to the entire ankle joint. [26][27][28] There is a research report that by collecting CT and MRI data of patients with ATFL rupture and 2-month follow-up after Broström surgery, by establishing nite element model of the foot and ankle to simulate the stress on the ankle joint of patients with ATFL injury before and after surgery during normal gait cycles (landing phase, neutral phase, off ground phase).…”
Section: Discussionmentioning
confidence: 99%
“…HU values are standardized linear attenuation coefficients for tissue [ 13 ]. Studies have reported the use of HU measurements to determine the subchondral bone density, in which specific stress distributional patterns of the medial gutter in the talocrural joint and the lateral aspect of the subtalar joints were studied in patients with chronic lateral ankle instability [ 14 , 15 ]. Previous studies on bone density analysis have revealed that the distal-dorsolateral area is the densest portion of the medial cuneiform [ 16 ].…”
Section: Introductionmentioning
confidence: 99%